Synergy Between The Government Of Prasung Village And PT Kemas Persada Internasional in The Implementation of Corporate Social Responsibility - Maria Novita Apriyani (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
Corporate social responsibility is an ongoing commitment by the business community to act ethically and contribute to the economic development of the local community or the wider community, along with improving the level of workers and their families. Companies in carrying out social responsibility, should focus on three things, namely profit (profit), society (people), and the environment (planet). Attention to the community and the environment around the company can be done one of them by the way the company carries out activities as well as making policies that can improve welfare, quality of life, and community competence in various fields. By paying attention to the environment, companies can participate in environmental preservation efforts for the sake of preserving the quality of human life in the long run. Law of the Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies and Government Regulation of the Republic of Indonesia Number 47 of 2012 concerning Limited Liability and Environmental Liability Companies as a legal umbrella for implementing Corporate Social Responsibility is no longer voluntary or philanthropic that depends on individual morals, but rather an obligation which must be carried out because it is mandatory. The company's obligation to implement the Corporate Social Responsibility is conveyed to the community through community service activities with the target audience, namely the people of Pasrung Village, Buduran District, Sidoarjo Regency. Education results from the synergy of village government programs with companies in implementing Corporate Social Responsibility, namely PT Kemas Persada Internasional has implemented Corporate Social Responsibility with several forms of programs including land clearing for community access, recruitment of workers from the local community. But the people of Pasrung village still don't understand the objectives and the form of Corporate Social Responsibility. If the community understands compliance with Corporate Social Responsibility, then the community can participate in formulate programs to match what is desired by society itself.